Advances in Cryogenic Engineering Materials 1998
DOI: 10.1007/978-1-4757-9056-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Welding Consumable Development for a Cryogenic (4 K) Application

Abstract: ABSTRACT. This paper summarizes the development and qualification of an appropriate welding consumable for a demanding cryogenic magnet application. It begins with a review of the research conducted on cryogenic fracture toughness of wrought and welded austenitic stainless steels. This research shows that certain elements of the composition have a powerful effect upon the steel's fracture toughness at 4 K. In particular, the higher oxygen content in the weld manifests itself as inclusions, which have a severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…[23,24] However, this 78 J is substantially lower than that of F316L (ca. 250 J), and is relatively close to the quoted recommended minimum standard.…”
Section: Discussionmentioning
confidence: 81%
“…[23,24] However, this 78 J is substantially lower than that of F316L (ca. 250 J), and is relatively close to the quoted recommended minimum standard.…”
Section: Discussionmentioning
confidence: 81%
“…The geometry of the model was defined in accordance with BS 10045. [32] Eight-node full integration elements were used to represent the specimen geometry; layers of elements were defined through the specimen thickness and were biased in thickness toward the outer surface of the geometry. A refined mesh arrangement was used such that the aspect ratio of the elements surrounding the V-notch tip was unity, with a minimum element size of 24 lm 9 17 lm 9 1 mm.…”
Section: Materials Flow Propertiesmentioning
confidence: 99%
“…It has been established that, 30% He improves fluidity and arc stability and allows a higher welding speed, 1-2% O 2 or 2-3% CO 2 increases the arc stability and 1-2% N 2 can improve mechanical and corrosion properties when welding nickel based and super duplex alloys [49]. Kane et al [56], reported that, welding of high nickel stainless steel alloy by pulsed GMAW was impossible using 100% argon due to arc instability also, it was reported that, the weldability improved when 1% CO 2 was added to the shielding gas mixture. Recommended shielding gas mixtures for various wire materials are given in Tables 3 and 4.…”
Section: Selection Of Shielding Gasmentioning
confidence: 99%